Idosos diabéticos: fatores predisponentes para amputações de membros inferiores - Almeida, Francisca das Chagas Alves de (2014)
Introduction: Population aging is a phenomenon of worldwide occurrence. In Brazil the changes in the characteristics of the population led to reduction of communicable diseases and elevation of chronic non-communicable diseases, among which stands out the diabetes mellitus, considered as serious public health problem. Objectives: Sociodemographic, economic and clinical characteristics of elderly diabetics undergoing lower limb amputation and investigating the factors that predispose the elderly diabetics to lower limb amputations. Methodology: A transversal descriptive study, quantitative, conducted with 103 seniors admitted in a reference hospital in the treatment of vascular disorders in the João Pessoa/Paraíba. For analysis it was used a statistical program, which has simple logistic regression. The results were discussed and confronted with other studies. Results: The study showed that 30.10% of participants were from João Pessoa, 52.43% female, 43.69% white, 47.57% married, 36.89% literate, 69.90% Catholics, 90.29% retirees, 77.67% hypertensive, 66.02% made use of oral hypoglycemic, 38.83% practiced physical exercise, 85.44% followed diet,84,47% controlled blood glucose and 77.67% frequented the Basic Health Unit, 47.57% used tobacco and 35.92% consumed alcoholic beverage. The uses of these substances are risk factors for lower limb amputations, while the early diagnosis of diabetes, blood sugar control and the intake of a proper diet are protective factors. Conclusion: The lower limb amputations in the elderly diabetics are related to the use of tobacco and alcohol, as well as the inadequate diet and the late diagnosis of the disease, in this sense, this research will guide the health team for planning targeted interventions to improve the quality of life of the elderly.